A participação dos portos secos na interiorização da logística das operações de importação e exportação: um estudo de caso - Antonia Dolores Belico Soares (2004)
At the moment that companies choose to internationalize their business, independent on the strategies that have motivated them to do it so, they have to be aware that the achievement of these business will demand a series of operational procedures present at harbors, dry ports, airports or borders. The operational success of an internationalnegotiation is intimately linked to the correct operation of the customs. Thus, this work investigates the participation of the dry ports in the act of carrying in the logistics of the import and export operations to the interior of the country, accomplished in the state of Minas Gerais. To fulfill this goal, a study of case following a qualitative and quantitative approach has been developed. In a first phase using detailed interviews with specialists in foreign trade, logistics and customs we have gathered the material that based the elaboration of the questionnaire applied to consolidate the collected observations. The first obtained results brought back a brief history of the implantation and effective working of thedry ports in the state of Minas Gerais. They have also revealed that the carry in of the logistics operations process of foreign trade of the state has been reduced with the privatization of Brazilian harbors, bringing significant consequences for the customs sites situated in the country. The main inducing factors of this inhibition were the bureaucracyexcess in the systematic that involves the import and export operations, as well as the precariousness of the services of transport and logistics that still are in force in the country.